2023
DOI: 10.1371/journal.pone.0280724
|View full text |Cite
|
Sign up to set email alerts
|

Problematic smartphone and social media use among undergraduate students during the COVID-19 pandemic: In the case of southern Ethiopia universities

Abstract: Background Smartphone and social media use are supposed to be integral parts of university students’ daily lives. More specifically, smartphones and social media are frequently used for communication in daily life during the COVID-19 pandemic. Nonetheless, uninterrupted and persistent use of these technologies may lead to several psychological problems. Even though smartphones and social media were used more frequently during the pandemic, there is no evidence suggesting that the studies were not undertaken in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The findings of Heffner et al ( 2021 ) are congruent with findings in Ghana reporting that large social media usage among female respondents increases COVID-19 fear levels (Malm et al 2022 ). Various studies reported that the excessive usage of social media during the COVID-19 pandemic was linked to high levels of anxiety among university students (Alhadi & Alhuwaydi 2021 ; Jiang 2021 ; Mengistu et al 2023 ). Mobile phone usage and accessing social media applications such as Facebook and Twitter drastically increased during the pandemic; access to a mobile device was important for students using online platforms for learning and social interactions (Jiang 2021 ; Mengistu et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Heffner et al ( 2021 ) are congruent with findings in Ghana reporting that large social media usage among female respondents increases COVID-19 fear levels (Malm et al 2022 ). Various studies reported that the excessive usage of social media during the COVID-19 pandemic was linked to high levels of anxiety among university students (Alhadi & Alhuwaydi 2021 ; Jiang 2021 ; Mengistu et al 2023 ). Mobile phone usage and accessing social media applications such as Facebook and Twitter drastically increased during the pandemic; access to a mobile device was important for students using online platforms for learning and social interactions (Jiang 2021 ; Mengistu et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with research prior to the pandemic indicating higher rates of IA among male students ( Liang et al, 2016 ; Vigna-Taglianti et al, 2017 ). However, Mengistu et al (2023) revealed an opposite trend by showing that only females were positively associated with problematic smartphone use during the pandemic. Besides, Shek et al (2023a) showed that gender was not related to IA in university students during the pandemic.…”
Section: Introductionmentioning
confidence: 90%
“…A study about the frequent usage of smartphones and social media was conducted to find out the causes of psychological problems among university students in Ethiopia. Depression, drug addictions, and urban residences were the influencing factors of problematic smartphone usage and poor sleeping quality significantly associated (Mengistu et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It affects health hazards like sleeping problems, reduced physical fitness, the habit of eating unhealthy foods, pain, migraines, depression, anxiety, drug addiction, addiction to social networking, and so on. (Kheirinejad et al, 2023;Kumar et al, 2011;Mengistu et al, 2023;Rathakrishnan et al, 2021;Shaheen et al, 2015;Tyagi et al, 2021;Vasudev et al, 2012;Wacks & Weinstein, 2021;Wang et al, 2019;Wattanaudomchai et al, 2023), and influences addictive behavior (Billieux et al, 2015;Servidio et al, 2022;Wattanaudomchai et al, 2023) decreasing face to face conversation with relatives and result increasing loneliness (Kim, 2017;Shaheen et al, 2015). Different types of diseases like heart diseases, effects on the fetus, alzherian's disease, Parkinson's disease, brain tumor, male infertility, and ear impairment, digital eye strain were caused by excessive use of mobile phones (Chowdhury et al, 2019;Mohan et al, 2021;Suhag et al, 2016;Tyagi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation